Fostering Employee Performance through a Growth Mindset: Co-worker Support and Campus Environment as Mediating Mechanisms - Juliandri Hasnur; Perengki Susanto; Rino Rino (Bulletin of Community Engagement, 2026)
This study investigates the effect of a growth mindset on employee performance, with coworker support and perceptions of the campus environment functioning as mediating variables among employees at two maritime polytechnics in Indonesia. The study aims to identify both the direct influence of growth mindset on performance and the mediating pathways conveyed by social support from colleagues and perceptions of the institutional environment. A quantitative survey using a structured questionnaire was conducted, and data were analyzed via Partial Least Squares–based structural equation modeling (PLS-SEM). Findings indicate that a growth mindset exerts a positive direct effect on employee performance and enhances both coworker support and perceptions of the campus environment; these two mediators significantly transmit the effect of growth mindset on performance, with the mediating role of the campus environment being more pronounced. In conclusion, fostering a growth-oriented mindset together with strengthening interpersonal relations among staff and improving institutional conditions constitutes an effective strategy to enhance employee performance in vocational institutions.